The Influence of Conversation Skills on Chatbot on Purchase Behavior in E-Commerce - Aulia Ramadhani; Putu Wuri Handayani; Ave Adriana Pinem; Puspita Kencana Sari (Jurnal Manajemen Indonesia, 2023)
To date, chatbots have been widely used in e-commerce as a replacement for conventional customer service agents. This study aims to analyze the influence of chatbots’ conversation skills on purchasing decisions made by e-commerce users. The specific skills examined were tailored response and response variety. This study used quantitative methods with online questionnaires and involved 699 respondents who had shopped on an ecommerce website and used a chatbot feature in the application. The e-commerce platforms involved in this study were the top five used in Indonesia: Shopee, Tokopedia, BliBli, Lazada, and Bukalapak. The data collected were analyzed using the partial least squares structural equation modeling method. The results show that the conversational skills of chatbots can influence consumer shopping decisions which can increase the sales of ecommerce organizations. The results provide guidance for e-commerce platforms using chatbots to help consumers with shopping. Keywords—Conversational Skills; Chatbot; E-Commerce; Indonesia; Purchase Behavior